A surfactant‐free synthesis of the silica nanosphere‐supported ultrafine silver nanoparticles and their antibacterial effects. Issue 8 (29th May 2019) - Shen, Qihui; Shan, Yixuan; Lü, Yang; Xue, Peng; Shu, Xian; Li, Dongmei; Liu, Yan; Liu, Xiaoyang
Abstract: In this study, a facile, efficient, and surfactant‐free method to synthesize silica nanosphere‐supported ultrafine silver nanoparticles (AgNPs) (~2.5 nm) was developed, and their antibacterial effects were investigated. In the synthesis process, the hydrolysis of 3‐mercaptopropyltrimethoxysilane was adopted to provide thiol groups and in situ reduce Ag + to Ag 0 for ultrafine AgNPs formation on the surface of the silica nanosphere. Electron microscopy characterization of the complex formed revealed that the ultrafine AgNPs were not agglomerated and grow without any surfactants because there were no excess electrons transported from the shell to reduce the silver ions to silver atoms. The antibacterial effects of the supported ultrafine AgNPs with the surfactant‐free surface were evaluated against the Escherichia coli even at very low dosage. After incubation with 20 μg/mL silica‐supported AgNPs up to 120 min, 99.7% of the E. coli were inactivated, according to the bacterial viability measured by flow cytometry. Abstract : A facile, efficient, and surfactant‐free method to synthesize silica nanosphere‐supported ultrafine silver nanoparticles (~2.5 nm) was developed. After incubation with 20 μg/mL silica‐supported AgNPs up to 120 min, 99.7% of the Escherichia coli were inactivated, according to the bacterial viability measured by flow cytometry.